Maintaining Professionalism on Facebook: Tips for Extension Agents - Amy Harder; Hannah S. Carter; Christy Chiarelli (EDIS, 2011)
Facebook has revolutionized the world in which we communicate. In just a few mouse clicks, you can access personal information, pictures, recent conversations, and much more about your Facebook “friends.” With these things in mind, it is important to carefully consider the implications of becoming a Facebook friend. This 4-page fact sheet discusses professionalism and legal considerations for using Facebook as a tool to promote Extension programs. Written by Amy Harder, Hannah S. Carter, and Christy Chiarelli and published by the UF Department of Agricultural Education and Communication, April 2011.